(3GdefJXe aj HOA GdOfjG hJhGQjN GdCees - (3eMeO Hf CMeO Hf EjGS GdMfaj GdeUQj, CHh GdHQcGJ,J (B930 (3g` s
(3ChdgG (B:s
(3CeG HYO agPG eLehY jMJhi Ydi TF ef eHOC GdNdb hefJgGg s
(3BNQgG (B:s
(3Je GdcJGH HMeO Gddg hYhfg, hMSf Jhajbg s
(3Vef eLehY , JQJjHgG (B: (3GdeLdO GdChds
(3HQSe GdNRGfI GdYGdjIGdYdejI OGhO Hf GdebQ YHOGdQMef Hf GdchjQs
(3dGHf Sgd GdHdNi GdeJhai Sf`(B344(3`Is
(3ef GdeQLM Cf GSe GdcJGH gh GdHOA hGdJGQjN ddeWgQ GdebOSi hGdPi WHY ai HGQjS efShHGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B5 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B236s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B295 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B1 s
Keywords: (3GdJGQjNs